Space efficient visualization of pedigree data - Claurissa Tuttle; Claudio Silva (2012)
A method of visually representing pedigree data is provided. A root individual in a genealogical dataset is identified. A first parent and a second parent of the identified root individual are identified from the genealogical dataset. A third parent and a fourth parent of the identified first parent are identified from the genealogical dataset. A pedigree visualization relative to the identified root individual is presented which includes a root indicator, a first parent indicator, a second parent indicator, a third parent indicator, and a fourth parent indicator. The first parent indicator is presented in a first direction relative to the root indicator, the second parent indicator is presented in a second direction relative to the root indicator, wherein the second direction is opposite the first direction, the third parent indicator is presented in a third direction relative to the first parent indicator, wherein the third direction is perpendicular to the first direction, and the fourth parent indicator is presented in a fourth direction relative to the first parent indicator, wherein the fourth direction is opposite the third direction.